Pengaruh Pengetahuan Dan Pelatihan Akuntansi Terhadap Penggunaan Informasi Akuntansi Usaha Mikro Kecil dan Menegan (UMKM) Di Kelurahan Kendis Dan Liningaan. - Tampubolon, Sonya; Jaqueline Tangkau; Cecillia Lelly Kewo (Papanda Publisher, 2025)
This study aims to analyze the influence of accounting knowledge and accounting training on the use of accounting information among MSMEs in Kendis and Liningaan. A quantitative approach with a causal associative design was employed. Data were collected from 40 MSME owners through questionnaires, observations, and documentation. The research instruments were tested for validity and reliability and analyzed using multiple linear regression after meeting classical assumption tests. The results indicate that accounting knowledge has a significant negative effect on the use of accounting information, while accounting training has a significant positive effect. Simultaneously, both variables significantly influence the dependent variable, with a coefficient of determination of 25%. These findings suggest that theoretical accounting knowledge does not always translate into practical application, whereas practice-based training more effectively enhances the utilization of accounting information. This study contributes to the literature on MSME accounting competencies and provides practical implications for designing more effective training programs.